2016
DOI: 10.1242/jeb.134775
|View full text |Cite
|
Sign up to set email alerts
|

Assessing hydrodynamic space use of brown trout, Salmo trutta, in a complex flow environment: a return to first principles.

Abstract: It is commonly assumed that stream-dwelling fish should select positions where they can reduce energetic costs relative to benefits gained and enhance fitness. However, the selection of appropriate hydrodynamic metrics that predict space use is the subject of recent debate and a cause of controversy. This is for three reasons: (1) flow characteristics are often oversimplified, (2) confounding variables are not always controlled and (3) there is limited understanding of the explanatory mechanisms that underpin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 61 publications
1
28
0
Order By: Relevance
“…Most studies of fish swimming and respirometry have used flowstraightening devices that result in low-turbulence flow conditions within the experimental setup, similar to the LTF condition described in this study. The natural habitat of most fishes is more turbulent than that created by such laboratory conditions, but most studies seeking to create more natural flows have focused on fish behaviour in coherent vortex structures, which represent only a small portion of the flows encountered by fish in their natural habitats (Lacey et al, 2012;Kerr et al, 2016). In predictable vortexdominated flows, it is common for fish to display energy-saving behaviour (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Most studies of fish swimming and respirometry have used flowstraightening devices that result in low-turbulence flow conditions within the experimental setup, similar to the LTF condition described in this study. The natural habitat of most fishes is more turbulent than that created by such laboratory conditions, but most studies seeking to create more natural flows have focused on fish behaviour in coherent vortex structures, which represent only a small portion of the flows encountered by fish in their natural habitats (Lacey et al, 2012;Kerr et al, 2016). In predictable vortexdominated flows, it is common for fish to display energy-saving behaviour (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have explicitly tested the effect of aperiodic, more randomized flow on fish swimming energetics and kinematics. Of these, many have suggested that fish should expend more energy in unsteady flows (Enders et al, 2003;Lupandin, 2005;Tritico and Cotel, 2010) or show greater variation among individuals (Kerr et al, 2016), as each fish must accommodate the unique flow structures it encounters.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations